Adverbia Bahasa Mooi: Adverbia Of Mooi Language - Yohanis Sanjoko (Balai Bahasa Provinsi Papua, 2022)
The aim of this study is to describe the adverb in Mooi Languge. This study is qualitative that used descriptive method with three stages, namely colllecting data, analyzing data, and presentating of data result. This study used face to face interview method and note tecnique to collect the data. To analyzed the data used shared method with immediate share component. According to analysis, adverb in Mooi, refers to its form, consist of two forms, they are word-base adverb and reduplication word adverb. Based on its syntax, adverb of Mooi has two positions. One is preceding adverb (on the left side of adverb) and another is following adverb (on the right side of adverb). In term of sense, Mooi language is able to express several meanings such as negation, calculation, limitation, degree, tense, entirely, probability, must, and frequency.